Removal of Pb(ii) from aqueous solution by mesoporous silica MCM-41 modified by ZnCl2: kinetics, thermodynamics, and isotherms1. Issue 46 (23rd May 2015) - Raji, Foad; Saraeian, Alireza; Pakizeh, Majid; Attarzadeh, Faridreza
<x xml:space="preserve">Abstract</x> ZnCl2-MCM-41 introduced itself as a high performance sorbent for Pb(ii) removal.